E-Learning for the Vision Impaired: A Holistic Perspective - Permvattana, Ruchi; Armstrong, Helen; Murray, Iain (Academic-Journal Org, 2012)
Problems faced by vision impaired students are different from those experienced by sighted students. Most e-learning environments are designed for sighted students, utilising complex visual images and interactive features. Unfortunately students with acute vision impairments are not able to utilise these features and must rely on applications with basic conversion facilities to translate the contents of screen displays and documents into forms that are accessible. Learning environments for people with physical disabilities need specific considerations in design and implementation to ensure their appropriateness and accessibility. This paper initially discusses specific problems faced by students with acute vision impairments and how e-learning environments need to address these problems in order for the student to achieve the same learning outcomes as sighted students. A brief outline of the research method undertaken is described. A model describing a comprehensive and holistic approach to e-learning environment design and development is then presented.